Does the tourist’s incivility relate to the tour guide’s professionalism? The case of destination Zanzibar - Abdalla, Moh’d Juma; Eluwole, Kayode K.; Öztüren, Ali (Inderscience Publishers, 2024)
As part of the service delivery process of tour operations, tour guides are often faced with rude behaviour from tourists. The present study develops a conceptual framework that empirically tests the linkages of tourist incivility (TIN), professional knowledge (TPK), professional attitude (TPA), and professional skills (TPS). Using SMART-PLS to analyse the data collected from 277 tour guides in Zanzibar, the study’s findings revealed that TIN has insignificant direct effects on both tour guides’ TPA and tour guides’ TPK. The results also suggest that TPS mediates the impact of tourist incivility on TPK but fails to support TPA mediation. Lastly, importance-performance map analysis revealed that TPK is of utmost importance to tour guides, although it leads to slightly lesser performance behind TPS and tourist incivility. Recommendations for novel coping mechanisms for practitioners were suggested. © © 2024 Inderscience Enterprises Ltd.
Keywords: incivility; professionalism; tour-guide; tourist; Zanzibar